Effect of feed modification on the behavior, blood profile, and telomere in horses exhibiting abnormal oral behaviors - Hanis, Farah; Chung, Eric Lim Teik; Kamalludin, Mamat Hamidi; Idrus, Zulkifli (Elsevier, 2023)
The physiological mechanism underlying the relationship between diet and abnormal oral behaviors (AOB) such as oral stereotypic (OS) and redirected behaviors (RB) in horses is relatively uncertain. Therefore, this study aims to elucidate the effect of diet modification on the behavioral changes, blood profile, hormonal concentrations, and relative telomere length in patrolling horses exhibiting AOB. A total of 12 patrolling horses were divided equally into the low AOB (n = 6; control) and the high AOB (n = 6; treatment) groups based on the mean time spent demonstrating OS and RB. Throughout the 30-day study, the high AOB horses were fed with a high forage high fiber (HFHF) diet, whereas the low AOB horses were fed with their normal allowance of high concentrate low fiber (HCLF) diet. The horses’ behaviors were recorded 3 days before the experiment commenced and was re-observed in the last 3 days of the experiment. Blood samples were collected before the feeding trial and post-feeding for the determination of hemato-biochemistry, plasma ghrelin, leptin and corticosterone concentrations, as well as the relative telomere length. Generally, High AOB horses fed with the HFHF diet exhibited a significant increase in bodyweight gain, whereas the mean proportion of time spent on OS and RB was significantly reduced. The feeding of the HFHF diet also significantly altered the hemato-biochemistry parameters of high AOB horses as compared to the pre-treatment and the control group fed with the HCLF diet. Post-treatment horses also revealed significantly lower plasma cortisol and ghrelin levels, but significantly higher plasma leptin levels. No significant association was found in the telomere length expression between AOB and type of diet. Conclusively, simple feed modification such as HFHF was able to influence the AOB, blood profile, and hormonal concentrations, which could ultimately improve the overall health and well-being of horses.